Ghost of a chance - Dixon, Franklin W. (Pocket Books, 2001)
"In the Tennessee woods, a movie about a daring thief lands the Hardys in danger!"
"A Minstrel book."
"In the Tennessee woods, a movie about a daring thief lands the Hardys in danger!"
Keywords: Detective and mystery stories.